Development of Kasab Tuah Kumita Craft Business in the District Three West Aceh Regency 2007-2024 - Lisa, Fona; Mawardi, Mawardi (Universitas Syiah Kuala, 2025)
Study This aiming to:know the birth process Tuah Kumita Community, know How development The Kumita Community from 2007-2024, and know what is the strategy of the Tuah Kumita Community still exist until now. Research This use method history with approach qualitative. Stages study covering election topic, collection sources, verification, interpretation, and historiography. Data collection techniques are carried out through documentation, interviews. Based on results Research:Tuah Kumita community, founded on January 1, 2007 by Wirda Yanti, aims to... to preserve art Aceh Police Chief and empower Mother House ladder post -tsunami. community This create opportunity Work from House while guard mark culture. The name